2004
DOI: 10.1385/bter:102:1-3:227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Extremely-Low-Frequency Magnetic Field on Antioxidative Melatonin Properties in AT478 Murine Squamous Cell Carcinoma Culture

Abstract: Effects of melatonin, extremely-low-frequency magnetic field (ELF-MF), and their combination on AT478 murine squamous cell carcinoma line were studied. Manganese superoxide dismutase (MnSOD), copper-zinc superoxide dismutase (Cu/ZnSOD), and glutathione peroxidase (GSH-Px) were used as markers of cells antioxidative status, and malondialdehyde (MDA) level was used as a marker of lipid peroxidation. After melatonin treatment, antioxidative enzyme activities were increased and MDA level was decreased. Application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Fasting obestatin and ghrelin levels were significantly lower in obese than in normal-weight individuals [21,[47][48][49]. Obestatin was negatively correlated with BMI, glucose, insulin, leptin, and the homeostasis model assessment of insulin resistance, and it was positively correlated with insulin sensitive index.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasting obestatin and ghrelin levels were significantly lower in obese than in normal-weight individuals [21,[47][48][49]. Obestatin was negatively correlated with BMI, glucose, insulin, leptin, and the homeostasis model assessment of insulin resistance, and it was positively correlated with insulin sensitive index.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…These might suggest a certain role of obestatin in the regulation of energy homeostasis. A significant relationship between plasma obestatin and ghrelin levels, independent of anthropometric parameters, supports simultaneous secretion of both hormones from the common precursor [21,[47][48][49][50][51]. However, Vicennati et al showed that obese women had higher obestatin levels, lower ghrelin blood levels, and a lower ghrelin/obestatin ratio compared with controls.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The 3 kHz -300 GHz range of electromagnetic radiation has been focused on; this range is referred to, for convenience, as radiofrequency electromagnetic fields (RF EMFs) [1]- [5]. Even if the existence of a clear and strong effect on embryonic development has not been widely accepted by the scientific community for RF [2] or extremely low frequency (ELF) (<300 Hz) magnetic fields with non-thermal intensities [4], several studies have shown that relatively low intensity EMFs are capable of interacting with molecular, cellular and systemic processes [6]- [9]. The primary issue that confronts this field is the lack of a conclusive understanding of the mechanism of interaction between EMFs and living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alterations in circadian rhythms which cause sleep disturbances have been observed in response to the EMF exposure (50/60 Hz) due to related decrease in melatonin levels (Burch et al 1999;Davis et al 2006) and cortical serotonergic neurotransmission (Janac et al 2009). Since melatonin is an antioxidant and its decrease is concomitant with accumulation of free radicals (PandiPerumal et al 2013), oxidative stress increases when exposed to EMF, hence supplementation of antioxidants were recommended under these conditions (Zwirska-Korczala et al 2004;Sokolovic et al 2008;El-Helaly and Abu-Hashem 2010;Kerman and Senol 2012). Interestingly, the EMF was not only reported to increase the life span of free radicals (Kabuto et al 2001;Stevens 2004), but was also involved in weakening the antioxidant defense mechanism (Lee et al 2004;Falone et al 2008), leading to increased oxidative stress condition (Blank and Goodman 2009;Martinez-Samano et al 2012).…”
Section: Introductionmentioning
confidence: 99%